Inner myometrial laceration – an unusual presentation of antepartum and postpartum hemorrhage: case reports and review of the literature. (17th August 2016) - Kaplanoglu, Mustafa; Kaplanoglu, Dilek; Bulbul, Mehmet; Dilbaz, Berna
Abstract: Objective : The aim of this study is to evaluate the diagnostic criteria, treatment options and progression of cases who have antenatal or postpartum hemorrhage due to internal myometrial laceration (IML) and to review the literature. Study design : The files of eight patients who were diagnosed to have IML between August 2012 and July 2015 were evaluated retrospectively. Results : The patient group consisted of four patients who had an emergency c-section due to massive bleeding during labor and four patients who had an emergency laparotomy due to uncontrolled bleeding after vaginal delivery after evaluation of the patient for signs of 4Ts (trauma, tissue retention, uterine tonus, and trombin). Primary suturation was the first-line treatment in all patients. In two of the patients, hysterectomy was performed after the defined surgical procedures were not successful in controling the bleeding. Conclusion : The presented case series is a pioneering study that describes IM which is a poorly defined reason of postpartum hemorrhage, as the cause of bleeding during labor. Primary suturation is the first-step, further surgery might be required in order to treat this life-threathening condition and the decision should be based on the age and the fertility status of the patient.